1996
DOI: 10.1210/endo.137.9.8756544
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 expression and modulation in human preovulatory follicles and ovarian cells.

Abstract: Just before the time of ovulation, the number of neutrophils increases markedly in the thecal layer of the leading follicle. A preovulatory rise in chemotactic activity for neutrophils in human follicular fluid has also been detected. We hypothesized that interleukin-8 (IL-8), a neutrophil chemoattractant/activating factor and a potent angiogenic agent, may be an important modulator of leukocyte chemotaxis in ovulatory function. In this regard we investigated the expression and modulation of IL-8 in human foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 23 publications
8
44
0
Order By: Relevance
“…The first is via prostaglandins which, by increasing vascular permeability, facilitate the follicular rupture and the second is via nitrogen oxide (NO) leading directly to follicular rupture. By the same token, TNF-a and IL-1b stimulate production of GM-CSF and IL-8, cytokines that will further facilitate ovulation and embryo implantation (Arici et al 1996). At that stage, IL-6 and IFN-g are also being detected in the endometrium possibly accounting for NO production .…”
Section: Cytokines In Ovulation Fertilization and Early Embryo Develmentioning
confidence: 99%
“…The first is via prostaglandins which, by increasing vascular permeability, facilitate the follicular rupture and the second is via nitrogen oxide (NO) leading directly to follicular rupture. By the same token, TNF-a and IL-1b stimulate production of GM-CSF and IL-8, cytokines that will further facilitate ovulation and embryo implantation (Arici et al 1996). At that stage, IL-6 and IFN-g are also being detected in the endometrium possibly accounting for NO production .…”
Section: Cytokines In Ovulation Fertilization and Early Embryo Develmentioning
confidence: 99%
“…It has been shown that neutrophils accumulate in the theca layer of the ovaries in humans and rats just prior to ovulation and that the expression of IL‐8 and CINC/gro, respectively, are responsible for this accumulation 4, 7, 8. Earlier reports have shown that IL‐8 and CINC/gro production are enhanced by human chorionic gonadotropin (hCG) 5, 9, 10. It also has been reported that CINC/gro production is increased by the addition of IL‐1 beta and tumor necrosis factor (TNF) alpha to cultures of whole ovarian dispersates 5…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ovulation is a well-recognized inflammatory process that is putatively modulated by cytokines. Numerous studies have demonstrated that a variety of proinflammatory cytokines, including interleukin (IL)-6, IL-8, IL-11, tumor necrosis factor (TNF)-α, leukemia inhibiting factor and the IL-1 system, are crucially involved in folliculogenesis (12), implantation (13) and follicular maturation (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%